2014
DOI: 10.5812/atr.18950
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Lead level in Patients With Retained Lead Pellets

Abstract: Background:Patients, who survived from shotgun injuries, often have some retained lead pellets in their bodies. Several cases of lead toxicity have been reported regarding these patients.Objectives:This study seeks to compare the serum lead level in patients who have retained lead pellets in their bodies with the control group.Patients and Methods:In this case-control study, we gathered the serum lead levels of 25 patients with some retained lead pellets in their bodies due to shotgun and 25 volunteers without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…This study shows that there were significantly higher BLLs in the test group than in the control group. This finding is in agreement with previous studies1819 where comparison of BLLs was done between those with and without retained lead missiles (pellets, bullets, and shrapnel) where higher BLL was seen in those with retained missiles in their bodies. This is expected since, in most developed and developing countries such as Nigeria, there is a reduction in environmental and occupational lead exposures due to the ban in leaded gasoline and the reduction in the use of lead in plumbing 20.…”
Section: Discussionsupporting
confidence: 93%
“…This study shows that there were significantly higher BLLs in the test group than in the control group. This finding is in agreement with previous studies1819 where comparison of BLLs was done between those with and without retained lead missiles (pellets, bullets, and shrapnel) where higher BLL was seen in those with retained missiles in their bodies. This is expected since, in most developed and developing countries such as Nigeria, there is a reduction in environmental and occupational lead exposures due to the ban in leaded gasoline and the reduction in the use of lead in plumbing 20.…”
Section: Discussionsupporting
confidence: 93%
“…The mean BLL of the study subjects was higher than that of their control counterpart (Table 2). This result is similar to the findings of Araújo et al, 15 Nguyen et al, 17 Moazeni et al, 20 and Farrell et al 12 Following the absence of occupational and environmental exposure of both the patients and their control subjects, the only possible explanation for the higher levels of lead among the patients is undoubtedly the presence of retained missiles.…”
Section: Discussionsupporting
confidence: 90%
“…In 2014, Moazeni et al[ 14 ] reported a comparison of 25 patients with some retained lead pellets in their bodies and the same number of volunteers without similar lead exposure. The results showed lead levels of 29 (± 12.8) μg/dL and 25.3 (± 6.4) μg/dL in case and control groups, respectively, without any significant difference (p = 0.3).…”
Section: Discussionmentioning
confidence: 99%
“…The reports of Moazeni et al . [ 14 ] and McQuirter et al . [ 6 ] found relations between exposure time and blood lead levels.…”
Section: Discussionmentioning
confidence: 99%